Fast contact localisation between deformable polyhedra in motion - Joukhadar, A.; Wabbi, A.; Laugier, C. (Proceedings Computer Animation '96, 1996)
This paper presents a new approach to detect and localise contact between concave deformable polyhedra. In this case there are many contact points between two polyhedra, the proposed algorithm detects and localises the contact in linear time O(n). It returns also the direction of this contact and the value of the maximum inter-penetration between the two convex-hulls of these two polyhedra.